Rip it up [compact disc] : the best of Specialty Records. - Price, Lloyd; Little Richard, 1932-2020; Milton, Roy; Cooke, Sam; Liggins, Joe; Mayfield, Percy, 1920-1984; Williams, Larry, 1935-1980 (Craft Recordings, 2021)
It brings together some of the most important tracks to be released on the notable Los Angeles record label. Founded in 1945 by Art Rupe, Specialty Records made a giant impact in the fields of gospel, rock n' roll, and R&B.